Influence of moisture on ferroelectric–paraelectric phase transition of a composite containing oxidized MWCNT and TGS. Issue 1 (30th April 2021) - Nguyen, Hoai Thuong; Thao, Phan Thi Bich
Abstract: This work reports experimental results for investigating the effects of residual water on phase transition in triglycine sulfate (TGS) filled with 5 wt% of oxidized multiwalled carbon nanotubes (OMWCNTs) under a relative humidity of 90% for different storage time. A similar composite containing TGS and non-oxidized MWCNT was also synthesized for comparison. According to measured data, the moisture was well adsorbed into OMWCNT/TGS composite and resulted in the shift of phase transition point toward higher temperatures for samples stored for less than 5 days. The longer storage caused a significant drop of dielectric constant at phase transition.